Current advances in seagrass research: A review from Viet Nam - Nguyen, Xuan-Vy; Phan, Thi Thuy Hang; Cao, Van-Luong; Nguyen Nhat, Nhu-Thuy; Nguyen, Trung-Hieu; Nguyen, Xuan-Thuy; Lau, Va-Khin; Hoang, Cong-Tin; Nguyen-Thi, My-Ngan; Nguyen, Hung Manh; Dao, Viet-Ha; Teichberg, Mirta; et al. (Frontiers in Plant Science, 2022)
Seagrass meadows provide valuable ecosystem services but are threatened ecosystems all over the world. This review highlights the current advances in seagrass research from Viet Nam. One goal is to support decision makers in developing science-based conservation strategies. In recent years several techniques were applied to estimate the size of seagrass meadows. Independent from the method used there is an alarming decline in the seagrass area in almost all parts of Viet Nam. Since 1990 a decline of 46.5% or 13,549 hectares was found. Only in a few protected and difficult to reach areas was an increase observed. Conditions at those sites could be investigated in more detail to make suggestions for conservation and recovery of seagrass meadows. Due to their lifestyle and morphology seagrasses take up compounds from their environment easily. Phytoremediation processes of Thalassia hemprichii and Enhalus acoroides are described as representative examples. High accumulation of heavy metals dependent on their concentration in the environment in different organs can be observed. On the one hand, seagrasses play a role in phytoremediation processes in polluted areas, on the other hand they might suffer at high concentrations and pollution will contribute to their overall decline. Compared with the neighboring countries, the total Corg stock from seagrass meadows in Viet Nam was much lower than in the Philippines and Indonesia, but higher than that of Malaysia and Myanmar. Due to an exceptionally long latitudinal coastline of 3,260 km covering cool to warm water environments, the seagrass species composition in Viet Nam shows a high diversity and a high plasticity within species boundaries. This leads to challenges in taxonomic issues, especially with the Halophila genus, which can be better deduced from genetic diversity/population structures of members of Hydrocharitaceae. Finally, the current seagrass conservation and management efforts in Viet Nam are presented and discussed. Only decisions based on the interdisciplinary cooperation of scientists from all disciplines mentioned will finally lead to conserve this valuable ecosystem for mankind and biodiversity.